PELATIHAN PEMBUATAN SABUN PADAT PELATIHAN PEMBUATAN SABUN PADAT ANTIBAKTERI BERBAHAN DASAR DAUN TEMURUI (Murraya koenigii) DI DESA LHOK BANIE, LANGSA BARAT, ACEH - Amna, Ulil; Safrida Sari, Mulia; Amri, Yulida; Fajriani Sukma, Fisca (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
Skin is the outermost part of the human body, skin will always be exposed to the environment surroundings, starting from exposure to sunlight, temperature, air humidity. Several factors cause dry skin, namely weather, including temperature and humidity, exposure to chemicals and microorganisms, aging, physiological and genetic stress. Efforts that can be made to improve skin conditions caused by microorganisms are the use of antibacterial cosmetics. One plant that can be used as an antibacterial is curry leaves or often known as "Temurui" which is the local name in the Aceh region for Murraya koenigii. The use of local natural resources as cosmetics is easy to develop, besides the basic ingredients are also easy to find in the Aceh region, including Lhok Banie Village. Making solid soap from temurui leaves is an effort to utilize the potential of local natural resources in Lhok Banie village to overcome the risk of spreading bacteria through the skin. Through PKM activities, it is hoped that it can increase community skills in processing temurui leaves into useful products that can be consumed personally and can also be marketed to improve the community's economy. This PKM activity is carried out in the form of direct training with the Lhok Banie community, especially PKK mothers and unproductive housewives. After that, this PKM activity also carried out community assistance with the hope that the community would receive solid soap in a sustainable manner as a regional superior product that would improve the community's economy